2018
DOI: 10.1177/0165551518762070
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating mobile music services in China: An exploration in user experience

Abstract: Most digital music repositories and services have mobile applications (apps) that facilitate convenient access for users via smartphones. Although China has one of the largest music listener populations in the world, there is little research evaluating Chinese online or mobile music services. To bridge this gap, this study evaluated mobile apps of three of the most popular Chinese music services from the user’s perspective, using usability testing and semi-structured interviews with a sample of active users in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 22 publications
0
4
0
1
Order By: Relevance
“…According to the study's researchers, students' sight-reading skills increased in both online and in-person courses [15]. When it was implemented in 2009, it was anticipated that the webconferencing software application would improve students' well-being and their ability to communicate with their teachers [16]. The use of digital technology allows online students to communicate with their teachers and classmates, thereby increasing their interest in academics while also cultivating a passion for music at the same time [17].…”
Section: Introductionmentioning
confidence: 99%
“…According to the study's researchers, students' sight-reading skills increased in both online and in-person courses [15]. When it was implemented in 2009, it was anticipated that the webconferencing software application would improve students' well-being and their ability to communicate with their teachers [16]. The use of digital technology allows online students to communicate with their teachers and classmates, thereby increasing their interest in academics while also cultivating a passion for music at the same time [17].…”
Section: Introductionmentioning
confidence: 99%
“…Namreč, razen v primerih istih avtorjev, niti v dveh člankih niso navedeni enaki vidiki uporabniške izkušnje. Dodatno so Betz in Hall (2015), Hu (2019) ter Hu in sodelavci (2017) sicer v teoretičnem delu govorili o pragmatičnih in hedoničnih vidikih uporabniške izkušnje, a so se potem v empiričnem delu ukvarjali izključno z uporabnostjo.…”
Section: Opredelitev Uporabniške Izkušnjeunclassified
“…Bauer (2014) explained that various musical instrument apps used in current society by young people, such as iTunes and Spotify, be regarded as a manifestation of collaborative possibilities. Hu (2019) further found that music mobile services such as QQ Music could enhance music information retrieval and provide users shareable digital libraries which have great potential for informal music learning. Pike and Shoemaker (2017) employed digital pianos, internet MIDI software, acoustic pianos and Skype video-conferencing software to teach primary students sight-reading in a distance learning mode.…”
Section: Using Technology In Music Educationmentioning
confidence: 99%